The religious text in the light of literary approaches, presentation and criticism - Hudhaili, Ass.Prof.Ali Hassen (Thi Qar Arts Journal, 2023)
The religious text is a linguistic text, so it can be analyzed in the way we analyze the literary text, especially since its expressions do not depart from being real or metaphorical, exactly as the literary text is, that is, its expressions are used, sometimes, in what they were intended for, and sometimes in a way other than what they were intended for. The text is not formed, and it does not perform its function except by meeting the truth with the metaphor. In clearer terms, what harm if we study simile or metaphor in the religious text, while preserving its sanctity and transcendence? The truth is that the problem begins with some scholars when they consider the religious text a truly human literary text, that is, it is the product of a human mythical imagination, which has nothing to do with heaven, and therefore it is a text that contains many myths and legends, so it needs a careful critical reading, and this is what It was carried out by Western interpreters, then it was transferred to Arab and Muslim secularists. Therefore, our study consisted of an introduction in which we talked about literary approaches and the main research question, then we moved on to analyzing theses of the two trends that studied the Qur’an in literature, the direction concerned with consolidating the faith reading of the Qur’an, and the direction based on doubt and critical tendency.